FACTORS INFLUENCING THE SUPPLY OF AGRICULTURAL CREDIT BY COMMERCIAL BANKS IN NIGERIA (1970 - 1993) - ISIJOLA , C. O.; IDOWU, E. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The main objective of this paper is to determine those factors influencing agricultural lending by commercial banks in Nigeria. Secondary data sourced from Central Bank of Nigeria's Publications spanning 1970 to 1993 were used. Ordinary Least Square regression analysis was used to estimate the agricultural credit supply function for commercial banks. The results obtained reveal that nominal interest rate on agricultural loans, minimum rediscount rate and liquidity ratio of commercial banks were the major factors influencing agricultural lending o' commercial banks in Nigeria.